MENELUSURI KEBAHAGIAN: ANALISIS MENDALAM TENTANG 'THE BOOK OF IKIGAI' DALAM BINGKAI SUBJECTIVE WELLBEING - Mita Tiara Kharisma Putri; Maria Oktasari; Nada Aulia Azzahra; Ahmad Haikal; Shafira Azzahra; Dina Ramadhani Fuhansyah (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
This study discusses the Japanese concept of Ikigai and its relationship with subjective well-being. The concept of Ikigai has five main aspects, namely starting small, freeing yourself, harmony and continuity, joy from small things, and being present in the present place and time. This research uses qualitative methods and analyzes the content of "The Book of Ikigai" to support its findings. The results show that the concept of Ikigai can be a foundation for individuals to achieve subjective well-being in daily life. By understanding and applying the principles of Ikigai, individuals can increase self-awareness, seek harmony, find joy from small things, and be present in the present place and time, all of which can contribute to the improvement of subjective well-being. The articles also cover various aspects of the Ikigai concept, including its effects on well-being, stress management, and performance, as well as its applications in the context of education and career choices. Some articles also explore the relationship between Ikigai and subjective well-being in various populations.